2021
DOI: 10.1111/scd.12629
|View full text |Cite
|
Sign up to set email alerts
|

Implant‐prosthetic treatment in patients with oral lichen planus: A systematic review

Abstract: Aims: This review is aiming on identifying the ideal implant-prosthetic treatment design in patients with OLP. Methods and Results: A systematic review was conducted using four electronic databases; Medline (PubMed), Cochrane library, DOAJ and SCOPUS, following the PRISMA statement recommendations to answer the PICO question: "which implant-prosthetic treatment design is most useful to ensure implant survival in OLP patients?". The study was pre-registered in PROSPERO (CRD 42020220102).Included articles qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…When the results of the abovementioned study and of the cases that developed oral squamous cell carcinoma were not considered, the dental implant failure rate in OLP patients was as low as 2.7% after a follow-up of five years, which is similar to populations without OLP (~2%) [ 30 ]. Recent systematic reviews reported a survival rate of dental implants placed in OLP patients of 98.9% after 38 months, 97.3% after 5 years, or 95.8% during a follow-up period ranging from 1 to 13 years [ 20 , 30 , 31 ]. The results from other systematic reviews and meta-analyses evaluating the outcomes of dental implants in OLP patients are provided in Table 2 [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When the results of the abovementioned study and of the cases that developed oral squamous cell carcinoma were not considered, the dental implant failure rate in OLP patients was as low as 2.7% after a follow-up of five years, which is similar to populations without OLP (~2%) [ 30 ]. Recent systematic reviews reported a survival rate of dental implants placed in OLP patients of 98.9% after 38 months, 97.3% after 5 years, or 95.8% during a follow-up period ranging from 1 to 13 years [ 20 , 30 , 31 ]. The results from other systematic reviews and meta-analyses evaluating the outcomes of dental implants in OLP patients are provided in Table 2 [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews reported a survival rate of dental implants placed in OLP patients of 98.9% after 38 months, 97.3% after 5 years, or 95.8% during a follow-up period ranging from 1 to 13 years [ 20 , 30 , 31 ]. The results from other systematic reviews and meta-analyses evaluating the outcomes of dental implants in OLP patients are provided in Table 2 [ 20 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations